The duty of care: a comparative common law analysis - Plunkett, J (2015)
The general aim of this thesis is to provide a detailed overview of the duty of care enquiry, drawing on both academic analyses and judicial experience in leading common law systems. The thesis starts by exploring the history of the duty concept, including how it first came to be an element of the negligence enquiry, and how it later came to be determined via the use of a general formula. The thesis then explores and analyses the various methods through which the existence of a duty of care has been determined. Having provided an overview of the development of the duty concept, it is then argued that the duty of care is best understood as consisting of two discrete parts: a factual aspect and a notional aspect. It is suggested that the factual aspect of the duty enquiry is superfluous and should be abandoned so that the duty enquiry is a notional issue only. It is then argued that the notional aspect of the duty enquiry is best understood as consisting of two separate types of determinations: those relating to broad situations, and those based on assumptions of responsibility. Both of these types of notional duty determinations are explored in detail. The propriety of basing situational notional duty determinations on considerations of policy, and the necessity of notional duty, are also considered. Finally, the thesis provides an overview of an empirical study of ultimate appellate court duty decisions, investigating, among other things, whether the understanding of duty provided in the thesis is consistent with the practice of the courts.